Architecture of peroxisomal alcohol oxidase crystals from the methylotrophic yeast Hansenula polymorpha as deduced by electron microscopy. - Vonck, J (1992)
The architecture of alcohol oxidase crystalloids occurring in vivo in the peroxisomes of methylotrophic yeasts was deduced from electron micrographs of similar crystals of the Hansenula polymorpha enzyme grown in vitro. Three characteristic views of the crystal are observed, as well as single layers in the very early stages of crystal formation. The crystal is concluded to be cubical, with every octameric molecule making the same contacts with four neighbors in one plane, at right angles to its fourfold axis. The unit cell contains six octamers, in three mutually orthogonal orientations, and two large holes, which can accommodate other peroxisomal proteins involved in methanol metabolism. The crystal contains channels, connecting the holes, which allow the diffusion of relatively large molecules through the crystal. Crystal formation depends on just one contact per subunit, which may explain the fragility of the crystals.